Doctoral examiners’ narratives of learning to examine in the PhD viva: a call for support - Tan, Wee Chun (Springer Nature, 2022)
This study aims to better understand the learning experiences of doctoral examiners in relation to their assessment practices in the PhD viva, which directly impacts the PhD candidates’ success in doctoral assessment. A narrative approach was employed to uncover the narratives of learning to examine in the PhD viva from twelve doctoral examiners in Malaysia. Based on the thematic analysis, examiners mainly learned from their own experiences and trial and error. Additionally, they hardly receive any institutional training on how to examine in the PhD viva. This suggests a need to support examiners, especially novice examiners, in their assessment endeavours. The findings contribute to the literature on doctoral examiner experiences by raising several important questions regarding examiner practices in the PhD viva and calling for institutional support. The study provides insights into how academic developers can support doctoral examiners more effectively in the PhD viva to ensure quality in doctoral assessment and a positive examination experience for doctoral examiners and candidates.